Detection and Differentiation of Frontotemporal Dementia and Related Disorders From Alzheimer Disease Using the Montreal Cognitive Assessment. (July 2016) - Coleman, Kristy K.L.; Coleman, Brenda L.; MacKinley, Julia D.; Pasternak, Stephen H.; Finger, Elizabeth C.
Abstract : The Montreal Cognitive Assessment (MoCA) is a cognitive screening tool used by practitioners worldwide. The efficacy of the MoCA for screening frontotemporal dementia (FTD) and related disorders is unknown. The objectives were: (1) to determine whether the MoCA detects cognitive impairment (CI) in FTD subjects; (2) to determine whether Alzheimer disease (AD) and FTD subtypes and related disorders can be parsed using the MoCA; and (3) describe longitudinal MoCA performance by subtype. We extracted demographic and testing data from a database of patients referred to a cognitive neurology clinic who met criteria for probable AD or FTD (N=192). Logistic regression was used to determine whether dementia subtypes were associated with overall scores, subscores, or combinations of subscores on the MoCA. Initial MoCA results demonstrated CI in the majority of FTD subjects (87%). FTD subjects (N=94) performed better than AD subjects (N=98) on the MoCA (mean scores: 18.1 vs. 16.3; P =0.02). Subscores parsed many, but not all subtypes. FTD subjects had a larger decline on the MoCA within 13 to 36 months than AD subjects ( P =0.02). The results indicate that the MoCA is a useful tool to identify and track progression of CI in FTD. Further, the data informs future research on scoring models for the MoCA to enhance cognitive screening and detection of FTD patients. Abstract : Supplemental Digital Content is available in the text.